المستوى التعليمي وعلاقته بتحقيق التنمية المستدامة - القرقوطي، البشير الهادي (جامعة جرش, 2015)
هدفت هذه الدراسة الوقوف علي اتجاهات الأفراد نحو المشاركة السياسية، وتعليم الأبناء، وتنظيم الأسرة التي تعزي لمتغير المستوي التعليمي، وتكونت عينة الدراسة من (220) عنصراً من أسرة كلية التربية، طرابلس، واستخدمت الدراسة المنهج الوصفي، وأداة الاستبيان، وأظهرت نتائج الدراسة وجود فروق جوهرية بين ممارسة الديمقراطية للأفراد، وتعليمهم للأبناء، وبين مستواهم التعليمي . كما أوضحت الدراسة عدم وجود فروق جوهرية بين تنظيم الأسرة، والمستوي التعليمي للأفراد، وأوصت بتقديم برامج لتوعية وتثقيف الفرد والأسرة بالتنمية المستدامة وأهميتها في الرفع من مستوي رفاهيتهم في الحاضر والمستقبل مع الحفاظ عبر الزمن بحقوق الأجيال القادمة.
The objectives of this study is to find out the differences in the attitude of individuals towards political participation, the education of boys and girls, and towards the family organization, in relation to the educational level variable. This study adopted the descriptive method approach, a questionnaire is also used to gather the required data, 220 subjects were participated. The study found out that there are significant difference regarding the political participation attributed to the educational level variable for the benefit of the most educated individuals among the researched sample, and found out also a significant difference regarding the boys and girls education also for the benefit of the most educated individuals among the researched sample. In addition, the study found out that there is no significant difference regarding the family organization attributable to the educational level variable. The study recommended that educational and awareness programs for individuals and families about the significance of the sustainable personal development must be provided.
Keywords: المستوى التعليمى -- التنمية المستدامة